2019
DOI: 10.1088/1612-202x/ab1bd7
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of dual-pump nonlinear amplifying loop mirror mode-locked all-fibre laser

Abstract: We numerically characterise, in the three-dimensional space of adjustable cavity parameters, the performance of a recently reported layout of a flexible figure-8 laser having two independently pumped segments of active fibre in its bidirectional ring [1]. We show that this optimisation problem can be efficiently addressed by applying a regression model based on a neural-network algorithm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Owing to its power of extracting essential information from large amounts of data, machine learning is bringing a revolutionary reform to research in the physical sciences [8]. In the field of photonics, a number of studies have been recently reported in laser design and optimization [9][10][11], complex nonlinear dynamics [12], design of photonic crystal fibers and optical components [13,14], pulse characterization [15], and optical communications [16,17]. In [18], we have shown that the combination of a graphical approach with the machine-learning method of neural networks (NNs) can provide a rapid and precise identification of the parameters of nonlinear pulse shaping systems based on pulse propagation in a normally dispersive fiber that are required to generate pulses with preset temporal features.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to its power of extracting essential information from large amounts of data, machine learning is bringing a revolutionary reform to research in the physical sciences [8]. In the field of photonics, a number of studies have been recently reported in laser design and optimization [9][10][11], complex nonlinear dynamics [12], design of photonic crystal fibers and optical components [13,14], pulse characterization [15], and optical communications [16,17]. In [18], we have shown that the combination of a graphical approach with the machine-learning method of neural networks (NNs) can provide a rapid and precise identification of the parameters of nonlinear pulse shaping systems based on pulse propagation in a normally dispersive fiber that are required to generate pulses with preset temporal features.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it enables reliable and reproducible live electronic adjustment of the lasing regimes. In this work, we numerically explore the broad range of operating states of the laser that can be accessed through independent control of the pump powers in the two gain segments and the laser output coupling ratio, β [12]. We use a piece-wise propagation model for the laser, in which propagation in the fibres follows a standard modified NLSE including gain saturation and spectral response for the active segments.…”
Section: Nonlinear Sculpuring In An All-fiber Figure-8 Lasermentioning
confidence: 99%
“…Machine learning algorithms have been already shown to be highly effective in solving optimization problems arising in photonics 23 27 . Particular type of the optimization algorithm should be chosen taking into account specific features of the fitness function.…”
Section: Introductionmentioning
confidence: 99%